Laryngopharyngeal reflux disease in the Greek general population, prevalence and risk factors - Spantideas, Nikolaos (BMC Ear Nose Throat Disord, 2015)
BACKGROUND: To assess the prevalence of laryngopharyngeal reflux (LPR) in the Greek general population and its risk factors. METHODS: Questionnaire based epidemiological, adult participants’ survey. The Reflux Symptom Index (RSI) was used for the assessment of LPR prevalence. The RSI questionnaire was completed by 340 (183 male and 157 female) randomly selected subjects. Subjects with RSI score ≥13 were considered as LPR patients and those with RSI score <13 were considered as non LPR subjects. RESULTS: The prevalence of LPR in the general Greek population was found to be 18.8 % with no statistically significant difference between the two genders (p > 0.05). The age group of 50–64 years showed the higher prevalence rate. Tobacco smoking and alcohol consumption were found to be related with LPR. No reported concomitant disease or medication was found to be related with LPR. CONCLUSIONS: LPR prevalence in the Greek general population was found to be 18.8 %. Tobacco smoking and alcohol consumption were found to be related with LPR.